2022
DOI: 10.3390/jof8111224
|View full text |Cite
|
Sign up to set email alerts
|

Pb Transfer Preference of Arbuscular Mycorrhizal Fungus Rhizophagus irregularis in Morus alba under Different Light Intensities

Abstract: Arbuscular mycorrhizal (AM) fungi can improve the lead (Pb) tolerance of host plants and accumulate intensive Pb in mycorrhizal roots. However, the detailed contribution of AM fungal extraradical hyphae to the plants’ Pb uptake remains unknown. In this study, mulberry (Morus alba) colonized by the AM fungus (Rhizophagus irregularis) with light treatments were linked by fungal extraradical hyphae using a three-compartment system (pot test), and their differences in responding to Pb application were compared. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…AMF has a certain tolerance to heavy metal stress, and a high concentration of Cd stress has a certain impact on the growth and development of AMF. Thus, high concentrations of heavy metals decrease the colonization of AMF in plant roots, but such findings may differ due to a wide variety of reasons, such as the compatibility of AMF species and plants, element concentration of metal and oxidation state, and environmental conditions [ 34 , 35 ]. Our results indicated that Cd treatment (50, 150, 300 μM) significantly increased AMF colonization compared with non-Cd treatment.…”
Section: Discussionmentioning
confidence: 99%
“…AMF has a certain tolerance to heavy metal stress, and a high concentration of Cd stress has a certain impact on the growth and development of AMF. Thus, high concentrations of heavy metals decrease the colonization of AMF in plant roots, but such findings may differ due to a wide variety of reasons, such as the compatibility of AMF species and plants, element concentration of metal and oxidation state, and environmental conditions [ 34 , 35 ]. Our results indicated that Cd treatment (50, 150, 300 μM) significantly increased AMF colonization compared with non-Cd treatment.…”
Section: Discussionmentioning
confidence: 99%